2011
DOI: 10.1002/lary.22252
|View full text |Cite
|
Sign up to set email alerts
|

CD147 Expression in Advanced Cutaneous Squamous Cell Carcinoma

Abstract: CD147 is upregulated in multiple cancer types, but its expression in advanced cutaneous squamous cell carcinoma (cSCC) is unknown. This study retrospectively evaluated the expression patterns of CD147 and related proteins monocarboxylate transporters (MCT1, MCT4) in patients with advanced stage cSCC (n=50). CD147, MCT1 and MCT4 expression levels were assessed in archived tumor samples and correlations were made with survival and clinicopathologic characteristics. The incidence of CD147 overexpression (93%, n=4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(33 reference statements)
1
4
1
Order By: Relevance
“…52 Some studies also indicate that CD147 is associated with an aggressive phenotype, increasing tumor proliferation, 53 migration, 54 invasion 55 and metastization, 56 as well as with poor survival in HNSCC. 36,57,58 In this study, no associations were found between CD147 and tumor aggressiveness or overall survival. GLUT1 mediates the important mechanisms involved in cellular glucose influx, allowing cells to proliferate and survive.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…52 Some studies also indicate that CD147 is associated with an aggressive phenotype, increasing tumor proliferation, 53 migration, 54 invasion 55 and metastization, 56 as well as with poor survival in HNSCC. 36,57,58 In this study, no associations were found between CD147 and tumor aggressiveness or overall survival. GLUT1 mediates the important mechanisms involved in cellular glucose influx, allowing cells to proliferate and survive.…”
Section: Discussioncontrasting
confidence: 59%
“…The plasma membrane expression of all proteins studied support their activity. Since most of the molecules here in studied, with the exception of MCT2, are involved in the cancer hyperglycolytic phenotype, one can assume that OCC have a highly glycolytic phenotype, which is supported by previous 27,[36][37][38][39][40] studies and by the applicability of FdG-PET scan in this type of cancer. [41][42][43] Moreover, since GLUT1 was present in 96.1% of tumor samples, this reinforces the presence of a glycolytic metabolism.…”
Section: Discussionsupporting
confidence: 56%
“…Staining for CD147, MCT1 and MCT4, among other markers, has been performed in pathological studies to determine the significance of these proteins in cutaneous SCC. Indeed, while these proteins have been suggested to serve as biomarkers of SCC and as targets of treatment, few studies to date have used antibodies against autophagy‐related molecules . In the present study, we performed immunohistochemical staining using LC3 and p62 antibodies in cutaneous SCC specimens resected at our hospital, collated the results and conducted statistical analysis to determine the significance of LC3 and p62 expression.…”
Section: Discussionmentioning
confidence: 98%
“…High emmprin expression in the tumor cells is associated with poor prognosis in SCC of the oral cavity, skin, and hypopharynx 29‐31 . The expression of CD73 not only in tumor cells but also in stroma affects prognosis.…”
Section: Discussionmentioning
confidence: 99%